Temporal Talbot effect applied to determine dispersion parameters - Cuadrado Laborde, Christian Ariel (2006)
The space–time duality theory and the temporal selfimaging phenomenon (or Talbot effect) are used to propose a method for determining dispersion parameters associated with an optic fiber link. From the space–time analogy, the actions of free-space propagation and phase curvatures taking place in the general spatial Talbot effect are implemented for time-varying wavefields. Using the temporal selfimaging conditions, a relationship is derived for determining the second-order dispersion coefficient of a given dispersive medium under test. As a particular application, we analyze the feasibility of the measuring approach using a linearly chirped fiber grating as the dispersive component under test. Some simulations are carried out in order to study the sensitivity and accuracy of the developed method.